Gendered Political Communication: A Study of the Coverage of Women Politicians in the Bangladeshi Press (Social Science Review, 2023)
This paper explores the processes of gender construction in political communication as reflected in the Bangladeshi media. It examines the coverage of female candidates during the 2018 general elections in four national Bengali-language newspapers using framing analysis and discourse analysis. It also includes interviews of nine women Members of Parliament to understand their response to the media coverage they do or do not receive in the national press, their own approaches to the media, and suggestions towards making the press more gender-sensitive in its political coverage. Based on the concept of gendered mediation, analysis of the media and interviews of women parliamentarians revealed that women politicians were framed in relation to male mentors; as new, inexperienced and potentially incompetent; and as representatives of women voters only. The findings suggest that the media should promote women more positively in politics by raising awareness of the presence, strength and efforts of women politicians, by covering in depth and evaluating their efforts, accomplishments and impact.Social Science Review, Vol. 39(3), Dec 2022 Page 55-72